Seismo-Acoustic Characterization of Mount Cleveland Volcano Explosions - Iezzi, Alexandra M.; Fee, David; Haney, Matthew M.; Lyons, John J. (Frontiers in Earth Science, 2020)
Volcanic explosions can produce large, ash-rich plumes that pose great hazard to aviation, yet may often have few precursory geophysical signals. Mount Cleveland is one of the most active volcanoes in the Aleutian Arc, Alaska (USA) with at least 65 explosions between December 2011 and June 2020. We characterize the seismo-acoustic signals from explosions at Mount Cleveland over a period of four years starting in 2014 when the permanent local instrumentation was installed. While the seismic explosion signals are similar, the acoustic signals vary between explosions. Some explosion acoustic waveforms exhibit a single main compressional phase while other waveforms have multiple compressions. The time lag between seismic and acoustic arrivals varies considerably (up to 2.20 s) at a single station ~3 km from the vent. We apply a variety of methods to explore the potential contributions to this variable time lag from atmospheric conditions, nonlinear propagation, and source depth within the conduit. This variable time lag has been observed elsewhere, but explanations are often unresolved. Our results indicate that while changes in atmospheric conditions can explain some of the variation in acoustic arrival time relative to the seismic signal arrivals, substantial residual time lag variations often still exist. Additionally, nonlinear propagation modeling results do not yield a change in the onset time of the acoustic arrival with source amplitudes comparable to (and larger) than Cleveland explosions. We find that a spectrum of seismic cross-correlation values between events and particle motion dip angles suggests that a varying explosion source depth within the conduit likely plays a dominant role in the observed variations time lag. Explosion source depths appear to range from very shallow depths down to ~1.5-2 km. Understanding the seismo-acoustic time lag and the subsequent indication of a variable explosion source depth may help inform explosion source modeling for Mount Cleveland, which remains poorly understood. We show that even with a single co-located seismic and acoustic sensor that does not always remain on scale, it is possible to provide meaningful interpretations of the explosion source depth which may help monitoring agencies understand the volcanic system during future times of unrest.